Psychological adaptation of the disabled in Sharon Draper’s Out of My Mind and Raquel Palacio’s Wonder: A comparative post-traumatic study - Alenezi, Majed; Elhalafawy, Ayman; Khalifa, Samir; Ismail, Sara; Alwethairi, Obaid; Algobaei, Faiz; Alrefai, Abeer A. (Research Journal in Advanced Humanities, 2026)
Referring to a post-traumatic study, the paper deals with the psychological adaptation of children with disabilities in Sharon Draper’s Out of My Mind (2010) and Raquel Palacio’s Wonder (2012). Post-Traumatic challenges the idea of idealism and tries to transform the negative perception of the idea of disability. Therefore, the study aims to examine the psychological adaptation of children with disabilities through a post-traumatic perspective. It claims that the stimulus of trauma in such stories is not a physical disability but a social marginalization, misidentification, and marginalization of feelings. The study determines the depiction of trauma, coping mechanisms, family support, and identity reconstruction process in each of the novels through a comparative literary analysis. Both novels break the stereotypes and move towards emotional regeneration as opposed to physical change. Focusing on how characters develop emotionally and oppose the normative expectations, Draper and Palacio re-establish disability literature as the place of agency, identity formation and narrative resistance. These conclusions imply that literature may transform cultural attitudes to disability by cultivating compassion, disrupting normative beliefs, and creating emotionally rich and multi-dimensional disabled characters.